Emodin attenuates inflammation and demyelination in experimental autoimmune encephalomyelitis - Yue-Ran Cui; Zhong-Qi Bu; Hai-Yang Yu; Li-Li Yan; Juan Feng (Neural Regeneration Research, 2023)
Emodin, a substance extracted from herbs such as rhubarb, has a protective effect on the central nervous system. However, the potential therapeutic effect of emodin in the context of multiple sclerosis remains unknown. In this study, a rat model of experimental autoimmune encephalomyelitis was established by immune induction to simulate multiple sclerosis, and the rats were intraperitoneally injected with emodin (20 mg/kg/d) from the day of immune induction until they were sacrificed. In this model, the nucleotide-binding domain-like receptor family pyrin domain containing 3 (NLRP3) inflammasome and the microglia exacerbated neuroinflammation, playing an important role in the development of multiple sclerosis. In addition, silent information regulator of transcription 1 (SIRT1)/peroxisome proliferator-activated receptor-alpha coactivator (PGC-1α) was found to inhibit activation of the NLRP3 inflammasome, and SIRT1 activation reduced disease severity in experimental autoimmune encephalomyelitis. Furthermore, treatment with emodin decreased body weight loss and neurobehavioral deficits, alleviated inflammatory cell infiltration and demyelination, reduced the expression of inflammatory cytokines, inhibited microglial aggregation and activation, decreased the levels of NLRP3 signaling pathway molecules, and increased the expression of SIRT1 and PGC-1α. These findings suggest that emodin improves the symptoms of experimental autoimmune encephalomyelitis, possibly through regulating the SIRT1/PGC-1α/NLRP3 signaling pathway and inhibiting microglial inflammation. These findings provide experimental evidence for treatment of multiple sclerosis with emodin, enlarging the scope of clinical application for emodin.